The Impact of the Transition and EU Membership on the Returns to Schooling in Europe - Harry Anthony Patrinos; Angelica Rivera-Olvera (Global Labor Organization (GLO), 2023)
Countries across Eastern Europe and Central Asia are in their third decade of independence. What impact does this have on the skills premium and does accession to the European Union have an impact on the returns to education? The returns to education in 28 transition and 20 non-transition countries in Europe and Central Asia are analyzed using panel data analysis and difference-in-difference methods to estimate the impact of transition and EU accession. It is found that the transition from a centrally planned economy to a market economy increases the returns to schooling in post-socialist countries positively and significantly, especially through the EU accession channel.
Keywords: I26; J31; O14; O33; 330; returns to education; transition; technological change